Identification of Students' Conceptual and Procedural Errors in Solving Problems in Three-Dimensional Material - Suhady, Wandy; Roza, Yenita; Maimunah, Maimunah (Green Publisher Indonesia, 2023)
Low math skills of students can be seen from the understanding and the assignment of students to a material. One of the clues to determine the extent to which students master the material is to analyze student's mistakes in working on. The study aims to describe the kind of conceptual errors and procedural errors in the student answered question on the three-dimesional material. This study used descriptive qualitative approach. This research subject is class XII IPA SMAN 1 Bengkalis. Techniques of data collection using interviews and documentation written test. The object of this study was grade XII IPA 1 SMAN 1 Bengkalis which amounted to 26 students. This research result is the kind of mistake that most people do students is a conceptual mistake in working on the three dimensional material is 52%. While its procedural errors as much as 48%. Conceptual errors and procedural errors occurred because of the low ability of abstraction and visual abilities in students in answering the questions that are hard to describe and determine the distance to a point on the field of three dimensional material. Low math skills of students can be seen from the understanding and the assignment of students to a material.